2008
DOI: 10.1111/j.1464-5491.2007.02348.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute hyperglycaemia and/or hyperinsulinaemia on proinflammatory gene expression, cytokine production and neutrophil function in humans

Abstract: Aims Type 2 diabetes is frequently associated with infectious complications. Swift activation of leucocytes is important for an adequate immune response. We determined the selective effects of hyperglycaemia and hyperinsulinaemia on lipopolysaccharide (LPS)-induced proinflammatory gene expression and cytokine production in leucocytes and on neutrophil functions.Methods Six healthy humans were studied on four occasions for 6 h during: (i) lower insulinaemic euglycaemic clamp, (ii) lower insulinaemic hyperglycae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 43 publications
3
91
0
2
Order By: Relevance
“…The study was approved by the Medical Ethical Committee of the Academic Medical Center in Amsterdam, and all subjects gave written informed consent. The present study was part of a study on effects of insulin and hyperglycemia on different parameters (31,32). The data in the present study, except for the glucose and insulin levels, have not been published previously.…”
Section: Subjectsmentioning
confidence: 73%
“…The study was approved by the Medical Ethical Committee of the Academic Medical Center in Amsterdam, and all subjects gave written informed consent. The present study was part of a study on effects of insulin and hyperglycemia on different parameters (31,32). The data in the present study, except for the glucose and insulin levels, have not been published previously.…”
Section: Subjectsmentioning
confidence: 73%
“…10,[25][26][27] Furthermore, recent cell studies have revealed that monocyte attachment with the vascular endothelial cells and the dysfunction of phagocytosis in neutrophils under the condition of hyperglycemia and hyperinsulinemia were associated with cytokine production in their cells. [14][15][16][17][18][19] However, it has not been determined whether insulin resistance can induce cytokine gene expression in leukocytes in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Cell studies have indicated that the induction of IL-1 and TNF-expression in neutrophils by hyperglycemia and hyperinsulinemia was associated with the dysfunction of phagocytosis in the cells. 18,19) Indeed, it is well known that monocyte/macrophage attachment to vascular endothelial cells and adipose tissues, and the dysfunction of phagocytosis in neutrophils can be found in patients and animals with diabetes. [20][21][22] These results indicate not only that diabetic conditions such as hyperglycemia and hyperinsulinemia lead to disturbance of the monocyte/macrophage and neutrophil functions, but also that cytokine expression in these cells may be concerned with this disturbance.…”
mentioning
confidence: 99%
“…From a haemodynamic perspective in the kidney, the influence of hyperglycaemia manifests as a hyperfiltration response characterised by a rise in filtration fraction [2][3][4][5][6], which may cause renal injury through shear-stress effects [7][8][9]. The haemodynamic effects of hyperglycaemia are attributed, in part, to activation of the renin-angiotensin-aldosterone system (RAAS) [6].…”
Section: Introductionmentioning
confidence: 99%